The Molecular Mechanism of FABP4 Inhibition Effects of GAS and 4-HBA in Gastrodia elata Blume Was Discussed Based on NMR and Molecular Docking - Yuyu Yang; Shihan Liu; Wenfang Jin; Zengyi Qu; Baolei Fan (Journal of Analytical Methods in Chemistry)
To isolate gastrodin (GAS), 4-hydroxybenzyl alcohol (4-HBA), and phenolic compounds from Chinese medicine Gastrodia elata Blume, and to explore the binding mode of fatty acid binding protein 4 (FABP4/aP2) that is closely related to macrophage inflammation, we study their anti-inflammatory targets. After the ultrasonic extraction of the main active components with 70% ethanol, three resins and three eluents were selected, and eight phenolic monomers with similar structures, such as gastrodin and 4-hydroxybenzyl alcohol, were isolated from Gastrodia elata by AB-8 macroporous resin and silica gel column chromatography and eluted with the CHCl3-MeOH gradient. Their structures were identified by HPLC and nuclear magnetic resonance (NMR). The FABP4 protein was added to GAS and 4-HBA, and the NMR experiment was performed to observe ligand binding. Finally, according to the spectral information of STD-NMR and molecular docking technology, the interaction between ligands and protein was studied. The fluorescence competition experiment confirmed that both GAS and 4-HBA were in the binding cavity of FABP4. Moreover, 3-phenoxy-2-phenylbenzoic acid (PPA) is a possible inhibitor of FABP4, reducing macrophage-related inflammation and endoplasmic reticulum stress. This work provides a new basis for the anti-inflammatory mechanism of Gastrodia elata, paving the way for the research and development of FABP4 inhibitor drugs.